Common positioning and technical errors in panoramic radiography - Pandey, S; Pai, KM; Dhakal, A (Journal of Chitwan Medical College, 2014)
Panoramic radiograph is one of the routinely used investigations in dentistry. The value of panoramic radiograph is reduced when they are of poor diagnostic quality. Therefore, the aim of the study is to be aware of the common positional and technical errors so as to minimize such errors occurring in the department. Panoramic radiographs of all the patients, who were taking radiographs for their own diagnostic purpose, were examined. All Radiographs taken for a 3 months period were 1010. All panoramic radiographs examined for various errors. Data were analyzed for the frequency of some common faults, both technical and processing errors, which directly contributed to failure of the radiographs. Total 1010 radiographs were analyzed for errors. 27.5% (n=278) were showing errors which ranged from technical errors 11.3% ( n=14) to positional errors 16.2% (n=164) and 72.5% of radiographs were error free. Most common technical error was density/dark radiographs which were 45% (n=51) and the most common positional error found was tongue not resting against the palate, 20% (n=32). Dark radiograph and tongue not resting against the palate were found common errors. Fewer errors are likely to be made when a quality assurance regimen and proper training, which includes the recognition and correction of errors, is followed DOI: http://dx.doi.org/10.3126/jcmc.v4i1.10844 Journal of Chitwan Medical College 2014; 4(1): 26-29